Digital Customs: Intelligent Systems and Technologies - Khashimjanova Madinabonu (European Science Publishing, 2024)
The processes of digitalization have covered all spheres of economic activity in the states. Undoubtedly, customs operations and customs control at the crossing of goods and citizens across customs borders today is accompanied by the use of software products and digital customs technologies. The current system is of great importance for ensuring economic security of the Republic of Uzbekistan, as this system provides not only the automation of document flow between participants of foreign economic activity and customs authorities, but also in tracking the movement of goods across customs borders using digital control units.
Keywords: customs authority, Uzbekistan-2030, artificial intelligence, IIR data analysis, AI customs responder, smart Bodyscanner, Blockchain technology.